Audit Quality and Earning’s Management After the Implementation of Key Audit Matters – Jakarta’s Public Accountants Perspective - Fakhri, Muhammad; Fitriany, Fitriany (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The development of SA 701, and changes to SA 700, has led to a greater emphasis on “Key Audit Matters” (HAU) in the independent auditor’s report. HAUs are the parts of the financial statements that are important and require more attention during the audit process. HAUs are considered to increase the transparency and usefulness of the auditor’s report for stakeholders, as well as assist the auditor in communicating significant risk areas during the audit. This study aims to analyse the factors that influence audit quality, earnings management practices, and the impact of HAU implementation on audit reports in Indonesia. This research uses qualitative methods with direct interview data collection with public accountants in the area around DKI Jakarta. the results of this research found that material errors are considered crucial in audit quality. HAU-related changes help to reduce errors. Views on auditor independence influenced judgements on audits and compliance with auditing standards was key.  The introduction of HAU is considered to increase transparency.